ABRASION INVESTIGATION USING SHEAR WAVE VELOCITY AND POISSON’S RATIO APPROACHES IN URAI VILLAGE NORTH BENGKULU REGENCY - Sesilia, Tiara; Farid, Muchammad; Hadi, Arif Ismul; Al Ansory, Andre Rahmat (Universitas Mataram, 2025)
The coastal areas of North Bengkulu Regency, particularly Urai Village, have been severely impacted by widespread abrasion, posing a high risk of coastal erosion within Bengkulu Province. This study aims to assess the extent of coastal degradation and support disaster mitigation efforts by investigating the properties and structure of rocks using geophysical methods, specifically the Multichannel Analysis of Surface Waves (MASW). The research focuses on determining shear wave velocity (Vs) to model the rock layers and produce a stratigraphic profile with a minimal misfit value. The obtained Vs30 values, ranging from 146 m/s to 603 m/s, indicate that the coastal region primarily comprises soft soils, which are highly susceptible to deformation, including abrasion. These findings provide essential data for understanding the underlying causes of coastal erosion and contribute to future disaster mitigation strategies.